1999
DOI: 10.5271/sjweh.379
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic exposures of potroom workers

Abstract: The following article refers to this text: 2008;34(6):463-470

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
2
15
2
Order By: Relevance
“…This is in agreement with other studies of coke oven workers (Zhang et al, 2001), iron foundry workers (Carstensen et al, 1999;Alexandrie et al, 2000) and asphalt workers (Burgaz et al, 1998). Similarly, we found that smoking had no significant effect the urinary 1-OHP levels of the control group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This is in agreement with other studies of coke oven workers (Zhang et al, 2001), iron foundry workers (Carstensen et al, 1999;Alexandrie et al, 2000) and asphalt workers (Burgaz et al, 1998). Similarly, we found that smoking had no significant effect the urinary 1-OHP levels of the control group.…”
Section: Discussionsupporting
confidence: 83%
“…These findings clearly indicate that the exposure of PAH is rather YP and GST polymorphisms and 1-OHP 515 high in coke oven workers and/or that, in Chinese coke oven workers, the use of protective equipment and proper clothing is poor. The lower levels of 1-OHP found in our study were similar to the mean urinary 1-OHP levels of Swedish aluminum factory workers (Carstensen et al, 1999;Alexandrie et al, 2000), probably explainable by the continuous use of protective equipment and clothing by the workers in our study. However, in our study 16% of urinary 1-OHP levels in coke oven workers still exceeded the occupational exposure limit (OEL) of 2.3 μmol mol -1 of creatinine (Jongeneelen, 2001).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Coke ovens, carbon electrode production plants, tar distillation plants, aluminum smelters, and creosote impregnation plants represent workplaces where high urinary 1-OHP levels are often observed. In a recent biomonitoring study of a Söderberg aluminum reduction plant in Sweden, urine samples from 96 pot-room workers and 5 control subjects were analyzed for 1-OHP (Carstensen et al 1999). Values observed (median, range) were 4.31 (0.09-17.7) µmol/mol creatinine for workers and 0.13 (0.06-0.75) µmol/mol creatinine for controls.…”
Section: Pah Exposure In Humansmentioning
confidence: 99%